Submicroscopic chromosomal imbalances in idiopathic Silver–Russell syndrome (SRS): the SRS phenotype overlaps with the 12q14 microdeletion syndrome. Issue 5 (16th September 2009) - Spengler, S; Schönherr, N; Binder, G; Wollmann, H A; Fricke-Otto, S; Mühlenberg, R; Denecke, B; Baudis, M; Eggermann, T
Abstract : Silver–Russell syndrome (SRS) is a heterogeneous disorder associated with intrauterine and postnatal growth restriction, body asymmetry, a relative macrocephaly, a characteristic triangular face and further dysmorphisms. In about 50% of patients, genetic/epigenetic alterations can be detected: >38% of patients show a hypomethylation of the IGF2/H19 imprinting region in 11p15, whereas the additional 10% carry a maternal uniparental disomy of chromosome 7. In single cases, cytogenetic aberrations can be detected. Nevertheless, there still remain 50% of SRS patients without known genetic/epigenetic alterations. To find out whether submicroscopic imbalances contribute to the aetiology of SRS, 20 idiopathic SRS patients were screened with the Affymetrix GeneChip Human Mapping 500 K array set. Apart from known apathogenic copy number variations, we identified one patient with a 12q14 microdeletion. The 12q14 microdeletion syndrome is characterised by dwarfism but it additionally includes mental retardation and osteopoikilosis. The deletion in our patient is smaller than those in the 12q14 microdeletion carriers but it also affects the LEMD3 and the HMGA2 genes. LEMD3 haploinsufficiency and point mutations have been previously associated with osteopoikilosis but radiographs of our patient at the age of 16 years did not reveal any hint for osteopoikilosis lesions. Haploinsufficiency of HMGA2 is probably responsible for aberrant growth in 12q14 microdeletion syndrome. However, in this study, a general role of HMGA2 mutations for SRS was excluded by sequencing of 20 idiopathic patients. In conclusion, our results exclude a common cryptic chromosomal imbalance in idiopathic SRS patients but show that chromosomal aberrations are relevant in this disease. Thus, molecular karyotyping is indicated in SRS and should be included in the diagnostic algorithm.